Examining the value of mental health awareness training for soccer coaching license candidates - Laura McLane; José M. Oliva-Lozano; Michele Kerulis; Rick Cost; Jessica Bartley; George Chiampas (Elsevier, 2024)
Many coaches encounter athletes and/or staff members with mental health concerns. Recognizing and referring individuals to support resources is vital for providing necessary assistance. Awareness and recognition of mental health issues enable coaches to create an inclusive and supportive environment where everyone can perform their best. This article examines the experiences of participants in U.S. Soccer's Coaching License Courses to understand the frequency they have experienced supporting athletes or staff with mental health challenges and their exposure, interest, perceived value to training in mental health awareness. This observational, cross-sectional study involved a survey following a free mental health awareness presentation. The results of this study showed: (a) a high prevalence of participants have supported athletes or staff in their environment with challenges related to their mental health (82.19 %); (b) a majority of participants had no previous training in recognition or management of mental health related issues (56.65 %); (c) a majority of participants worked with youth athletes (60.16 %); and (d) nearly all participants felt that there was value in having training in mental health for their role as a coach or administrator (98.71 %). In conclusion, coaches and administrators in soccer desire more mental health awareness training. The prevalence to which they have supported individuals with mental health challenges emphasizes the continued need for training and access to mental health resources. Additionally, incorporating training and awareness into all coaching license levels should be prioritized, making it a requirement to comprehensively support athletes and staff both on and off the field.